The order of time [compact disc, unabridged] - Rovelli, Carlo, 1956- (Penguin Audio, 2018)
Time tends to be considered uniform and universal, but it may be much more complicated than that. In fact, the more scientists learn about it, the more mysterious it becomes. In lyric, accessible prose, Rovelli invites us to consider questions about the nature of time that continue to puzzle the best minds.